(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
This study aims to shed light on the employment of the senses and to examine their aesthetic and technical functions in narrative discourse in the absence of visual perception. It seeks to identify the types of imagery that can substitute for visual representation within the artistic and emotional structure of the text. The study adopts a descriptive-analytical approach, supported by a comparative methodology to strengthen the analysis and enhance the validity of the findings. It investigates the use and interaction of the senses (synesthesia) in Ghassan Kanafani’s “The Blind and the Deaf” and Hooshang Golshiri’s “A Cellar for the the Otter” The findings indicate that the remaining senses compensate for the absence of sight through their ability to convey imagery and emotional experience in an indirect manner. Hearing emerged as the most frequently employed sense in the narratives, followed by touch. The study also reveals that substituting one sense for another results from the capacity of certain senses to encompass and convey visual or emotional experience more effectively than others. Further detailed findings will be presented in the full study.